Peace Values in Bugis and Makassar Perspective - Buchori, Sahril; Fakhri, Nurfitriany (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2018)
This study aims to produce a description of the values of peace based on the perspectives of Bugis and Makassar ethnic figures. The scope of the study includes the values of peace within the Bugis pappaseng and Makassar's pappasang, as well as other values of peace as the basis of living together. The research method used is qualitative descriptive that describes the peaceful cultural values of the Bugis and Makassar. Data collection in the form of interview and documentation (study of literature). Participants in this study amounted to five figures from the Bugis and Makassar. The results of the study show that Bugis and Makassar have peaceful values as the foundation and guidelines for Bugis and Makassar people to live together in peace. The values of peace of Bugis and Makassar ethnic in the form of values of mutual respect, respect, mutual admonition, mutual respect, affection, loving god, unity, cooperation, and mutual cooperation.